Níveis de Beta-glucanos em dietas de leitões de 21 a 60 dias de idade - Clara Bandeira Silva Mendes (2008)
One experiment was realized with 1,500 animals distributed in experimental blocks at random with five treatments: control, 60, 120, 180 and 240 grams of beta-glucan per ton of feed. The analyzed variables were daily weight gain, final weight, daily feed consumption and feed conversion in periods of 21 to 35, 21 to 49 and 21 to 60 days old. We noticed a significantly linear increase in the final weight and the daily weight gain of piglets supplemented with betaglucan in the diet of 21 to 60 days old. The inclusion of 240 grams of beta-glucan per ton of feed provided a final weight increase of 800 grams, which corresponds to an increase of 3.2% compared to the control group. The daily weight gain was 4.7% higher for the group of animals treated with 240 grams of beta-glucan per ton of feed. There was no significant treatment effect on the daily consumption of feed, feed conversion, activity of the superoxide dismutase enzyme, immune response or on the intestinal morphology (heigh of villosity and depth of crypt).